Incidence of Acquired Nontraumatic Spinal Cord Injury in Finland: A 4-Year Prospective Multicenter Study - Niemi-Nikkola, Ville; Koskinen, Eerika; Väärälä, Eija; Kauppila, Anna-Maija; Kallinen, Mauri; Vainionpää, Aki (Archives of physical medicine and rehabilitation, 2021)
To evaluate the incidence and epidemiologic characteristics of acquired nontraumatic spinal cord injury (NTSCI) in Finland. Prospective 4-year epidemiologic multicenter study. Two of the 3 spinal cord injury (SCI) centers in Finland responsible for acute care, immediate rehabilitation, and lifelong follow-up for all SCI patients in a population of 3,073,052 (as of 2013). All newly diagnosed NTSCI patients (N=430) admitted to Tampere University Hospital between 2012 and 2015 and Oulu University Hospital between 2013 and 2016 based on the evaluation of the designated rehabilitation teams. Patients with NTSCI resulting from congenital etiologies or progressive neurologic diseases were excluded. Not applicable. Incidence and variables, according to the International SCI Core Data Set and the International Standards for Neurological Classification of SCI, including etiology and the severity of injury. The incidence of NTSCI was 54.1 per million per year. NTSCI was more common in men (n=260, 60.5%) than women (n=170, 39.5%). The mean age was 62.0±14.6 years old. Degenerative causes were the most common etiology (n=219, 50.9%), followed by malignant (n=88, 20.5%) and benign (n=41, 9.5%) neoplasms. The injury resulted in tetraplegia in 177 patients (41.1%) and paraplegia in 249 patients (57.9%). American Spinal Injury Association Impairment Scale grade D injuries were common, with an incidence of 71% (n=304). Specialized inpatient rehabilitation was needed in 44% (n=189) of the cases. There are no previous studies on the epidemiology of NTSCI in Finland, and international reporting has been limited. The incidence of NTSCI in our study was substantially higher than in most previous studies, which was likely owing to our study including individuals with less severe lesions who did not require inpatient rehabilitation.